Antibiotic Resistance Pattern of Bacteria Causing Urinary Tract Infections in Children of Fasa During the years 2012 and 2014 - alireza molazade; abbas shahi; sohrab najafipour; farzane mobasheri; Fateme Norouzi; sara Abdollahi Kheirabadi; seyed jalal-; mohammadSaeed gholami (Fasa University of Medical Sciences, 2014)
Background & Objectives: Urinary Tract Infection (UTI) is one of the most prevalent bacterial infection in children. Awareness of the antibiotic resistance of common bacteria causing UTI in each area has a large impact on infection improvement. The objective of this study is to evaluate the antibiotic resistance of bacteria causing UTI in two to 15 years old children referring to Fasa Vali-e-Asr hospital during 2012 and 2014. Materials & Methods: This cross sectional - descriptive study was done on 283 children with UTI that had positive urine culture. After identification of strains, the antibiotic sensitivity definition test, using antibiogram disk diffusion method, was done. Results: In this study, the most frequent isolates were Escherichia coli 64.3%, Klebsiella 14.5%, and staphylococci 6.4%. The highest sensitivity rate was to Ciprofloxacin and Nitrofurantoin and the highest resistance was to Co-trimoxazole and Cefalotin. Conclusion: Regarding the results, it is recommended to use Ciprofloxacin and Nitrofurantoin for outpatient treatment of UTI. Selecting proper antibiotics for UTI treatment should be on the basis of the local prevalence of pathogenic bacteria and antibiotic resistance pattern.